PENGARUH BRAND ATTACHMENT TERHADAP REPURCHASE INTENTION PADA KOPI KENANGAN DENGAN BRAND COMMITMENT DAN BRAND LOYALTY SEBAGAI VARIABEL INTERVENING - Novan Yurindera (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Kopi Kenangan became the first Foods and Beverages Retail Unicorn from Southeast Asia, during the COVID-19 pandemic, the company learned to quickly adapt to changing business environments and challenges by implementing new strategies, so as to be able to serve 40 million cups of coffee in the last 12 months. This study aims to determine whether Brand Attachment through Brand Commitment and Brand Loyalty has an effect on Repurchase Intention of Kopi Kenangan. The research method is quantitative with the independent variable is Brand Attachment, the intervening variables are Brand Commitment and Brand Loyalty, and the dependent variable is Repurchase Intention. The population in this study were Kopi Kenangan consumers with a sample of 200 respondents. Data collection was carried out using a questionnaire which was distributed using a Google form. Data processing uses the SEM method by utilizing the SmartPLS application which consists of outer model analysis, inner model analysis and hypothesis testing. The results showed that Brand Attachment through Brand Commitment and Brand Loyalty indirectly affected Repurchase Intention on Kopi Kenangan, but Brand Attachment directly did not affect affected Repurchase Intention on Kopi Kenangan.